Bacterial dispersal and drift drive microbiome diversity patterns within a population of feral hindgut fermenters. Issue 2 (20th December 2020) - Stothart, Mason R.; Greuel, Ruth J.; Gavriliuc, Stefan; Henry, Astrid; Wilson, Alastair J.; McLoughlin, Philip D.; Poissant, Jocelyn
Abstract: Studies of microbiome variation in wildlife often emphasize host physiology and diet as proximate selective pressures acting on host‐associated microbiota. In contrast, microbial dispersal and ecological drift are more rarely considered. Using amplicon sequencing, we characterized the bacterial microbiome of adult female ( n = 86) Sable Island horses (Nova Scotia, Canada) as part of a detailed individual‐based study of this feral population. Using data on sampling date, horse location, age, parental status, and local habitat variables, we contrasted the ability of spatiotemporal, life history, and environmental factors to explain microbiome diversity among Sable Island horses. We extended inferences made from these analyses with both phylogeny‐informed and phylogeny‐independent null modelling approaches to identify deviations from stochastic expectations. Phylogeny‐informed diversity measures were correlated with spatial and local habitat variables, but null modelling results suggested that heterogeneity in ecological drift, rather than differential selective pressures acting on the microbiome, was responsible for these correlations. Conversely, phylogeny‐independent diversity measures were best explained by host spatial and social structure, suggesting that taxonomic composition of the microbiome was shaped most strongly by bacterial dispersal. Parental status was important but correlated with measures of β‐dispersion rather than β‐diversity (mares without foals had lower alpha diversity and more variable microbiomes than mares with foals). Our results suggest that between host microbiome variation within the Sable Island horse population is driven more strongly by bacterial dispersal and ecological drift than by differential selective pressures. These results emphasize the need to consider alternative ecological processes in the study of microbiomes.